Transient flow of evaporating fluid in multiple parallel pipes, theory and experiments. (November 2020) - Hayat, Ron Rene; Barnea, Dvora; Taitel, Yehuda
Abstract: The model of Barnea et al. [1] for an evaporating liquid flow in a system of parallel heated pipes with common inlet and outlet headers was modified, taking into account fluctuations in the flow rates during the transient process. The experimental system of two horizontal parallel mini channels presented in Barnea et al. [1] was expanded to include four pipes. New quantitative data on the steady state flow rate distribution and the transient response of the system to changes in the inlet flow rate and in the heating power are presented. The degree of complexity of three and four parallel heated pipes increases significantly compared to the case of two pipes. Several stable steady state flow rate distributions may be obtained for the same inlet flow rate, as well as various transient trajectories towards these steady states. The experimental results compare fairly well with the modified model simulations. The possibility of having multiple transient routs for the same constraint in the operational conditions is illustrated.